(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2015)
The natural durability of timber may be defined as ‘inherent resist ance of timber to attack by wood deterioration agents such as wood decaying fungi and wood destroying insects’. In Malaysia, natural durability of timber is determined using a ‘graveyard’ test . The average time taken for this test is more than 10 years. The results of this test method do not provide information on longevity (service life) either out of ground contact, or in other geographical locations. Comparison of natural durability requires the use of standard test method where for example in Europe, the accepted laboratory method is EN 350-1. This paper briefly describes the rating of natural durability based on comparison results of the two test methods stated i.e the exterior graveyard test and the interior laboratory test.